La experiencia regulatoria en Perú - Fernández-Baca, Jorge (1998)
This article examines the Peruvian regulaton; policy making since 1993, when the government initiated a new period of structural reforms aiming at consolidating the adjustment and liberalization processes. We emphasize the case of the Institute for the Defense of Competition and the Protection of Intellectual Property (Indecopi), because this is the regulatory agency with the biggest accumulated experience in the solution of conflicts and the enforcement of sanctions.